Produção de celulases através da fermentação em estado sólido utilizando como substrato sorgo lignocelulosico - Santin, Franciane Maria Mantovani (Universidade Federal do Tocantins, 2020)
The solid state cultivation of the filamentous fungus isolated from the nest of leaf-cutting ants of the species Acromyrmex balzani was carried out, using lignocellulosic sorghum as a substrate aiming at the maximum production of cellulases, through the optimization of the cultivation process, evaluating the influence of the variables: initial concentration inoculum, humidity, time, pH and temperature. The effects of the variables were first evaluated in terms of the activity of the FPase enzyme, where humidity and time were statistically significant at 95%. In conditions of greater time and humidity, the enzymatic activity decreases showing a negative effect. The other variables did not show a statistically significant effect at 95% confidence. The greatest enzymatic activities were provided by the combination of the variables of test 2, which presents humidity 60%, pH 4, incubation time of 4 days, initial inoculum concentration of 108 and temperature of 40oC. The significant variables were subsequently optimized. In the second part of the experiment, the activity of the FPase enzyme showed the best response with the moisture content of 60 and 75%, and the incubation time 4 to 6 days, with a maximum productivity of 4.1 IU / g. The CMCase activity showed maximum activity between 55 and 65% humidity and with an incubation time of 5 to 8 days, reaching an enzymatic activity of 4.1 IU / g. As for Avicelase activity, the highest production was with the moisture content around 65 and 80% and with the incubation time of 2 to 5 days, reaching an enzymatic activity of 3.8 U / g. The activities presented demonstrate an expressive cellulolytic capacity of the studied fungus, compared to lignocellulosic sorghum.